Brain Functional Alteration at Different Stages of Neuropathic Pain With Allodynia and Emotional Disorders - Zhang, Ya-Nan; Xing, Xiang-Xin; Chen, Liu; Dong, Xin; Pan, Hao-Tian; Hua, Xu-Yun; Wang, Ke (Frontiers in Neurology, 2022)
Neuropathic pain (NeuP), a challenging medical condition, has been suggested by neuroimaging studies to be associated with abnormalities of neural activities in some brain regions. However, aberrancies in brain functional alterations underlying the sensory-discriminative abnormalities and negative emotions in the setting of NeuP remain unexplored. Here, we aimed to investigate the functional alterations in neural activity relevant to pain as well as pain-related depressive-like and anxiety-like behaviors in NeuP by combining amplitude of low frequency fluctuation (ALFF) and degree centrality (DC) analyses methods based on resting-state functional magnetic resonance imaging (rs-fMRI). A rat model of NeuP was established via chronic constriction injury (CCI) of the sciatic nerve. Results revealed that the robust mechanical allodynia occurred early and persisted throughout the entire observational period. Depressive and anxiety-like behaviors did not appear until 4 weeks after injury. When the maximum allodynia was apparent early, CCI rats exhibited decreased ALFF and DC values in the left somatosensory and nucleus accumbens shell (ACbSh), respectively, as compared with sham rats. Both values were significantly positively correlated with mechanical withdrawal thresholds (MWT). At 4 weeks post-CCI, negative emotional states were apparent and CCI rats were noted to exhibit increased ALFF values in the left somatosensory and medial prefrontal cortex (mPFC) as well as increased DC values in the right motor cortex, as compared with sham rats. At 4 weeks post-CCI, ALFF values in the left somatosensory cortex and DC values in the right motor cortex were noted to negatively correlate with MWT and exhibition of anxiety-like behavior on an open-field test (OFT); values were found to positively correlate with the exhibition of depressive-like behavior on forced swimming test (FST). The mPFC ALFF values were found to negatively correlate with the exhibition of anxiety-like behavior on OFT and positively correlate with the exhibition of depressive-like behavior on FST. Our findings detail characteristic alterations of neural activity patterns induced by chronic NeuP and underscore the important role of the left somatosensory cortex, as well as its related networks, in the mediation of subsequent emotional dysregulation due to NeuP.